(untitled) (Jurnal Bina Praja, 2023)
This study was conducted in the context of Indonesia, which has entered the final stage of the three-period bureaucratic reform. Although progress has been made in various fields, indicators show that Indonesia still needs to achieve the ideal standard in terms of bureaucratic reform. The study aims to analyze the developing reform bureaucracy from the perspective of government dynamics to evaluate the Indonesian government’s efforts and identify the factors that become obstacles in the bureaucratic bureaucracy. Researchers use NVivo to map the practices of dynamic governance in Indonesia based on the systematic literature review (SLR) results. The results showed that the Indonesian government has begun to apply a dynamic governance approach in contextualizing and implementing the bureaucracy. However, resistance to change and past habits from the New Order era became an obstacle to bureaucratic reform. The results also showed that corruption is a fundamental problem that is still being faced in Indonesian culture and needs to be addressed immediately in efforts to reform the bureaucracy.